Beaches of the Black and Azov Seas in the Modern Russian Tourism Industry Structure: Current State and Development Prospects - Aleksandrovna Volkova, Tatiana; Yuryevich Belikov, Mikhail; Aleksandrovich Mishchenko, Alexander; Vladimirovna Minenkova, Vera; Anatolyevich Filobok, Anatoly (International Journal of Engineering and Technology, 2018)
The state of the tourism industry reflects the level of the tourism development on a certain territory. Over the recent years the tourism industry of the Russian Federation has changed considerably. The Krasnodar Territory as one of the leading tourist regions of the country has general national trends, too. The number of holidaymakers at the Azov-Black Sea coast resorts has grown. Territorial development of the tourist and recreational complex of the Azov-Black Sea coast is characterized by unevenness: a great flow of tourists come to rest on beaches of the Black Sea of the Krasnodar Territory in the high season. It is possible to conditionally divide the beaches of the Black Sea coast in the Krasnodar Territory into five districts. A lot has been done to improve the level of beach service and landscaping. The general condition of beaches depends more on private entrepreneurs renting beaches.